21.0k views
5 votes
What are the first two steps in solving the radical equation below?

√x - 6 +5 = 12
Look at picture(15 points)

What are the first two steps in solving the radical equation below? √x - 6 +5 = 12 Look-example-1
User Murolem
by
4.4k points

2 Answers

5 votes

Answer:

B. Subtract 5 from both sides and then square both sides.

Explanation:

First, subtract 5 from both sides in order to get
√(x-6)=7^(2)

Second, square both sides in order to get
x-6=49 (p.s. squaring both sides gets rid of the square root)

Third, add 6 to both sides in order to get x=55

Last, see that the answer is B, as you had to subtract 5 from both sides and then square both sides to get your answer

There you go, and good luck on the other questions!

User Mostafazh
by
4.9k points
4 votes

Answer:

B

Explanation:

Given


√(x-6) + 5 = 12 ( subtract 5 from both sides )


√(x-6) = 7 ( square both sides )

x - 6 = 49 ( add 6 to both sides )

x = 55

User Bholtbholt
by
5.1k points